DIDACTIC SCAFFOLDING LEADERSHIP PEDAGOGY: - G.E. Dames (Acta Theologica)
This is a collaborative retrospective/introspective study of over forty years of spiritual and faith learning and teaching in search of answers to the following questions: Why did so many of the youth Coetzee (2019) taught develop into some of the most prominent leaders at all levels of South African society? What did he do right? How did he construct his teaching ministry? Hermans’ (2003) didactics of learning as a theoretical learning theory is employed as a theoretical framework in response to the above research endeavour. Coetzee’s (2019) methodology (hereafter, the Y-model) is applied as a case study of didactic scaffolding.  The Y-model serves as an example of how faith education can support contemporary religious education as a relevant and meaningful alternative to producing authentic and successful leaders.